The influence of family income on the career choice of students at universities of technology - Shumba, Almon; Naong, Matsidiso (South African Journal of Higher Education, 2016)
Students’ future career aspirations and expectations are essential precursors of adult attainment. The study sought to determine the impact of poverty influences the ability of children to pursue their preferred career choices. A cross-sectional study amongst Education students was conducted at three universities of technology in South Africa. The study sample comprised of 141 students. The study found that 69.2% bemoan lack of or inadequate family income as the most common impediment towards realising their chosen career choices. Furthermore, 34.8% ranked teaching as the highest, followed by Engineering with 14.2% and Accounting/Finance with 11.3%. Through life-skills courses and programmes, learners should not only be exposed to various career choices, but also made aware of available sources of finance such as bursaries and loans.